Peri-operative analgesic efficacy of tramadol in dogs and cats - Chen, H. C.; Ong, B. H. E.; Kaka, U. (Veterinary Association of Malaysia, 2020)
Tramadol, classified as an 'atypical opioid', is a centrally acting analgesic that is easily available in injectable and oral preparations in Malaysia. Queries on its use and efficacy to manage pain in small animal practice prompted this review. Following tramadol administration in dogs, there is lack of sedation and opioid effects when compared to cats. This may likely due to species difference in the production, metabolism and elimination of O-desmethyltramadol (M1). Good efficacy of tramadol was reported in both dogs and cats undergoing ovariohysterectomy and castration. Pre-emptive doses were administered via parenteral routes between 2 - 4 mg/kg, usually during premedication or after induction. Adequate pain control was reported with tramadol 2 mg/kg, SC every 8 hours following maxillectomy or mandibulectomy in dogs. Thus, adequate analgesia can be promoted with increase doses or repeated parenteral dosing following orthopaedic procedures. Repeated oral doses of tramadol as the sole analgesic were found to be less effective in dogs undergoing tibia plateau levelling osteotomy. Combinations of tramadol and a non-steroidal anti-inflammatory drug were found to provide better post-operative analgesia in both dogs and cats.